PENGARUH TANGIBLES, RELIABILITY, RESPONSIVENESS, ASSURANCE, EMPHATY TERHADAP KEPUASAN, LOKASI DAN LOYALITAS NASABAH BANK PANIN YOGYAKARTA - Gumilang, Sonia (-)
This research is aimed to tes the effects of Tangibles, Reliability, Responsiveness, Assurance, Emphaty towards nasabahâ€™ satisfaction, location, loyalty.This research uses prime dataquestionnaire and involves 42 nasabah of Bank Panin Yogyakarta as sample respondents dan using (validity, reliability, t, F, R square and pathways) as data analysis methods.t test results : tangibles, reliability, responsiveness, satisfaction and location have a significant positive effect toward loyalty. Assurance and emphaty have a significant negative effect toward loyalty. F test results : tangibles, reliability, responsiveness, assurance, emphaty, satisfaction and location simultaneously affect significantly loyalty. R square test results 0,998, means loyalty variabels and described by tangibles, reliability, responsiveness, assurance, emphaty variabels with satisfaction and location as an interval variabels 99,8% and the rest 0,20% discribed by other external factors. Pathway analysis results : direct effect of application tangibles, reliability, and responsiveness to loyalty is more effective. Direct effect of tangibles to llyalty is the most dominant effect.Keywords : tangibles, reliability, responsiveness, assurance, emphaty, satisfaction, location,Â  loyalty